Aberrant Neural Response to Social Exclusion Without Significantly Greater Distress in Youth With Bipolar Disorder: Preliminary Findings - Roybal, Donna J.; Cosgrove, Victoria E.; Kelley, Ryan; Smallwood Shoukry, Rachel; Larios, Rose Marie; Novy, Blake; Chang, Kiki D.; Garrett, Amy S. (Frontiers in Psychiatry, 2022)
Background Little is known about the effects of social exclusion on youth with bipolar disorder (BD). Understanding these effects and the functional neural correlates of social exclusion in youth with BD may establish differences from healthy youth and help identify areas of intervention. Methods We investigated brain function in 19 youth with BD and 14 age and gender matched healthy control (HC) participants while performing Cyberball, an fMRI social exclusion task. Whole brain activation, region-of-interest, and functional connectivity were compared between groups and examined with behavioral measures. Results Compared with the HC group, youth with BD exhibited greater activation in the left fusiform gyrus (FFG) during social exclusion. Functional connectivity between the left FFG and the posterior cingulate/precuneus was significantly greater in the HC compared with the BD group. For the HC group only, age and subjective distress during Cyberball significantly predicted mean FFG activation. No significant differences in distress during social exclusion were found between groups. Conclusion Although preliminary due to small sample size, these data suggest that youth with BD process social exclusion in a manner that focuses on basic visual information while healthy youth make use of past experiences to interpret current social encounters. This difference may account for the social cognitive issues experienced by youth with BD, which can lead to more severe anxiety and mood symptoms.